Peranan Badan Kehormatan Dewan Perwakilan Rakyat Daerah (DPRD) dalam Menjaga Marwah Anggota DPRD Provinsi Sulawesi Tengah - Lestari, Novi; Lasatu, Asri; Muhammadong, Nasrullah; Andhini, Resmi Yustie (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the role of the Honorary Board (Badan Kehormatan) of the Regional House of Representatives (DPRD) of Central Sulawesi Province in maintaining the dignity and accountability of its members as public officials. The urgency of this topic lies in the increasing number of ethical violations and political behavior that potentially erode public trust in regional legislative institutions. The study adopts an empirical legal research method with a qualitative descriptive approach, collecting data through interviews, documentation, and literature review. The findings reveal that the Honorary Board plays a crucial role as an internal ethical guardian by overseeing members’ conduct, enforcing the code of ethics, and ensuring institutional integrity. However, several challenges persist, including limited authority in enforcement, lack of coordination with other DPRD bodies, and insufficient public transparency in the decision-making process. The study also highlights that the case of Yahdi Basma’s alleged misconduct exemplifies the complexities of political ethics within regional legislative frameworks. Overall, the research emphasizes the need to strengthen the institutional capacity of the Honorary Board through clearer regulations, community participation, and transparent evaluation mechanisms to uphold the DPRD’s moral and ethical credibility. The results contribute to the broader discourse on legislative accountability and ethical governance at the regional level in Indonesia.